Motyw męskości w estetyce cottagecore. Badania memetyczne - Pawluk, Zofia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Popularity of specific Internet aesthetics could indicate current beliefs of certain social groups. Researching the newest popular cottagecore aesthetic it is hard not to observe an emerging relationship between genders. The women’s movement which aims towards escaping big city life seems not to include men in their fantasy of rural living and independence. A noticeable absence of male representation and their conscious exclusion is partially explained through cottagecore content created by women. The aim of this article is to analyse the core ideas of the aesthetic in the context of modern perception of masculinity. The text includes description of the two only male creators in the circle of the aesthetic on the TikTok platform. The methodology is based on identifying Internet aesthetics as memes according to Richard Dawkins’s definition.
The theme of masculinity in the cottagecore aesthetic. Meme studies
Keywords: aesthetic; meme; masculinity; cottagecore; Internet